A formal model for intellectual relationships among knowledge workers and knowledge organizations. (April 2015) - Li, Mao-Lin; Yung, Duncan; Chang, ShiKuo
Abstract: An academic learning network consists of multiple knowledge organizations and knowledge workers. The intellectual relationships can be derived from the interactions among them. In this paper, we propose a formal model to describe the interactions in an academic learning network and further provide an evaluation process to quantify intellectual relationships. Our approach is also integrated with a realistic social network platform SMNET.